2012
DOI: 10.1038/cgt.2012.19
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-β lipofection II. Mechanisms involved in cell death and bystander effect induced by cationic lipid-mediated interferon-β gene transfer to human tumor cells

Abstract: Interferon-b lipofection II. Mechanisms involved in cell death and bystander effect induced by cationic lipid-mediated interferon-b gene transfer to human tumor cells MS Villaverde, ML Gil-Cardeza, GC Glikin and LME FinocchiaroWe evaluated the cytotoxic effects (apoptosis, necrosis and early senescence) of human interferon-b (hIFNb) gene lipofection. The cytotoxicity of hIFNb gene lipofection resulted equivalent to that of the corresponding addition of the recombinant protein (rhIFNb) on human tumor cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 38 publications
(43 reference statements)
2
22
0
Order By: Relevance
“…A previous study showed that cytotoxic effects (e.g. apoptosis, necrosis, and early senescence) of human IFNβ gene lipofection showed the same or a superior effect to that of high doses of the exogenously applied recombinant IFNβ protein [76]. Based on these findings, the researchers also found that fIFN-ω lipofection and expression is equal to or more effective than rFIFN-ω protein at suppressing cell growth by inducing ROS generation, mitochondrial potential disruption and calcium uptake [77].…”
Section: Biological Activities Of Type I Ifnsmentioning
confidence: 99%
“…A previous study showed that cytotoxic effects (e.g. apoptosis, necrosis, and early senescence) of human IFNβ gene lipofection showed the same or a superior effect to that of high doses of the exogenously applied recombinant IFNβ protein [76]. Based on these findings, the researchers also found that fIFN-ω lipofection and expression is equal to or more effective than rFIFN-ω protein at suppressing cell growth by inducing ROS generation, mitochondrial potential disruption and calcium uptake [77].…”
Section: Biological Activities Of Type I Ifnsmentioning
confidence: 99%
“…Thus, rFeIFN-ω may be used as a therapeutic agent in feline and canine mammary carcinomas. There is evidence showing that gene transfer would allow one to take advantage of the beneficial effects of type I IFNs without their undesirable side effects [52]. For instance, HuIFNβ gene lipofection produces an equal or even superior effect than that of high doses of exogenously applied HuIFNβ protein.…”
Section: Anti-proliferation and Antitumor Activity Of Ifn-ω In Bench mentioning
confidence: 99%
“…For instance, HuIFNβ gene lipofection produces an equal or even superior effect than that of high doses of exogenously applied HuIFNβ protein. Recently, a study conducted by Villaverde et al [52] demonstrated that felines FeIFN-ω gene lipofection exhibited an equal or higher cytotoxic effect than rFeIFN-ω. This kind of effect was due to the induction of reactive oxygen species generation, mitochondrial membrane potential disruption, and calcium uptake, indicating that fFeIFN-ω lipofection is an alternative approach for treating both sensitive and resistant phenotypes with an equal or superior outcome and with fewer adverse effects than recombinant fFeIFN-ω therapy [52].…”
Section: Anti-proliferation and Antitumor Activity Of Ifn-ω In Bench mentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with the fact that the great bystander effect of the hIFNb gene lipofection involves the production of reactive oxygen species, simultaneous with a mitochondrial potential decrease in both cell lines. 39 The combination antineoplastic drug/hIFNb gene in the chemotherapy-sensitive cells (monolayers of EW7) displayed only additive or counteractive effects. This suggests that, when cells do not exhibit resistance, the cytotoxic mechanisms triggered by hIFNb gene lipofection may be saturating the signaling pathways.…”
Section: Discussionmentioning
confidence: 99%